Eco-friendly and cost-efficient inks for screen-printed fabrication of copper indium gallium diselenide photoabsorber thin films - Gonçalves, Bruna Ferreira (2021)
Given the societal concerns about the use of toxic chemicals and costly processing during the fabrication of functional materials and devices for photovoltaic applications, it is important to develop alternative sustainable methodologies. Previous studies have shown that cost-effective printing fabrication of Cu(In,Ga)Se2 thin film photovoltaics represent an interesting alternative to the energy-demanding vacuum-based deposition methods, commonly used to produce Cu(In,Ga)Se2 photovoltaics. To enrich the field of printed Cu(In,Ga)Se2 photoabsorber thin films and to develop associated eco-friendly solutions, two novel inks, consisting of non-toxic reagents and readily available oxide materials, are reported. Screen printing of the inks over fluorine-doped tin oxide conductive substrates followed by swift selenization of the resultant patters provides a straightforward route to produce phase-pure, uniform, and compact Cu(In,Ga)Se2 films with thickness and band gap energies ranging from 2.5 µm to 3.5 µm and from 0.97 eV to 1.08 eV, respectively. The present approach represents an important step for the sustainable fabrication of Cu(In,Ga)Se2 photovoltaics, where the physical properties of the photoabsorber can be easily adjusted by tuning the conditions of the screen printing process and the metal ratios in the inks.